Microbowls with Controlled Concavity for Accurate Microscale Mass Spectrometry. Issue 12 (10th February 2022) - Xu, Linfeng; Li, Xiangpeng; Li, Wenzong; Chang, Kai‐chun; Yang, Hyunjun; Tao, Nannan; Zhang, Pengfei; Payne, Emory M.; Modavi, Cyrus; Humphries, Jacqueline; Lu, Chia‐Wei; Abate, Adam R.
Abstract: Patterned surfaces can enhance the sensitivity of laser desorption ionization mass spectrometry by segregating and concentrating analytes, but their fabrication can be challenging. Here, a simple method to fabricate substrates patterned with micrometer‐scale wells that yield more accurate and sensitive mass spectrometry measurements compared to flat surfaces is described. The wells can also concentrate and localize cells and beads for cell‐based assays. Abstract : Patterned surfaces can enhance the sensitivity of laser desorption ionization mass spectrometry by segregating and concentrating analytes, but their fabrication can be challenging. A simple method to fabricate substrates patterned with micrometer‐scale wells that yield more accurate and sensitive mass spectrometry measurements compared to a flat surface or cylindrical wells is presented. The wells can also concentrate and localize cells and beads for cell‐based assays.